SEROPREVALENCIA DE Neospora caninum EN CANINOS DE DOS DISTRITOS DE LA PROVINCIA DE CHACHAPOYAS - Horna M., Segundo (2003)
Neospora caninum is a parasite of dogs that causes high rates of abortion and neonatal mortality in cattle throughout the world. The objective of the study was to determine the prevalence of Neospora caninum in dogs from districts of Molinopampa and Leymebamba, province of Chachapoyas, Amazonas. A total of 142 serum samples were evaluated (63 from Molinopampa and 79 from Leymebamba) for the detection of antibodies using the indirect immunofluorescence test (IFAT). The 28.9 ± 7.5% of the animals were positive to N. caninum. A seroprevalence of 34.9 ± 11.8% and 24.1 ± 9.4% were found in dogs of Molinopampa and Leymebamba districts, respectively. This results demonstrate the existence of a high seroprevalence of dogs infected with Neospora caninum in the region.